Determining the influence of structure on hybridization using oligonucleotide arrays. - Mir, K; Southern, E (1999)
We have studied the effects of structure on nucleic acid heteroduplex formation by analyzing hybridization of tRNAphe to a complete set of complementary oligonucleotides, ranging from single nucleotides to dodecanucleotides. The analysis points to features in tRNA that determine heteroduplex yield. All heteroduplexes that give high yield include both double-stranded stems as well as single-stranded regions. Bases in the single-stranded regions are stacked onto the stems, and heteroduplexes terminate at potential interfaces for coaxial stacking. Heteroduplex formation is disfavored by sharp turns or a lack of helical order in single-stranded regions, competition from bases displaced from a stem, and stable tertiary interactions. The study is relevant to duplex formation on oligonucleotide microarrays and to antisense technologies.